F(-6)if(3)=4x+7

Simple and best practice solution for F(-6)if(3)=4x+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for F(-6)if(3)=4x+7 equation:


Simplifying
F(-6) * if(3) = 4x + 7

Reorder the terms for easier multiplication:
-6 * 3F * fi = 4x + 7

Multiply -6 * 3
-18F * fi = 4x + 7

Multiply F * fi
-18fiF = 4x + 7

Reorder the terms:
-18fiF = 7 + 4x

Solving
-18fiF = 7 + 4x

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Divide each side by '-18iF'.
f = -0.3888888889i-1F-1 + -0.2222222222i-1xF-1

Simplifying
f = -0.3888888889i-1F-1 + -0.2222222222i-1xF-1

See similar equations:

| y+2=2y-7 | | 3.8x=2.7x+5.5 | | 2/5(-15d)= | | 3(a+2)+2(3a-1)= | | x-7/5-2=x-9/4 | | (9x^2y-5xy+4xy^2)-(4x^2y+10xy+3xy^2)= | | 1/3x-7=6 | | 3x^2-108x+2187=0 | | 1.1x=0 | | 7n^2+62n-80= | | 3x^2-108x-2187=0 | | 2y^2+36=0 | | 10(s-7)=6s-66 | | x^2-36x+729=0 | | (-2.6x+2)(-4)= | | 2*7/8 | | (4x+8)+7x+3= | | 2mx7/8m | | 7-x/10=x+9/5 | | X/t=f | | 2m*7/8m= | | 32a^4b-18b^3=0 | | 6z-3=4z+8 | | 1c+1=-2c+19 | | 9x+8x+4x-5= | | 56-4x=6-4x | | x^4+3x^3+2x^2-3x+1=0 | | 11m+6n-4m+9n= | | 31=-18x^2+4x | | [2ln(1-x)]+ln(2x-3)-ln(x+1)=[2ln(3)] | | 21x^2-162x-48= | | -2-3x-2=-2x+8-k |

Equations solver categories